HUBUNGAN ANTARA PENDIDIKAN KESEHATAN DENGAN TINGKAT PENGETAHUAN TENTANG PENYAKIT DIABETES MELLITUS: RELATIONSHIP BETWEEN HEALTH EDUCATION AND KNOWLEDGE LEVEL ABOUT DIABETES MELLITUS - Yestiani Norita Joni; Muhammad Kaisar (Jurnal Nurse, 2021)
Diabetes Melitus is impaired glucose, protein, and lipid metabolism that characteristic by hyperglycemia condition that need long term treatment. Health Education have positive impact on knowledge as the basis of health behavior. this study aims to assess the affact of health education on knowledge of type 2 Diabetes Melitus patients. this study use quantitative approach study with pre experimental one group pre post test study design one time education. Samples of this study were 12 respondents which choosen by purpossive sampling thecnique. Evalution of knowledge score was mesured using DQK-24 with 24 item question. paired T test use to assess differences knowledge score. The result of this study showing there is defference mean of knowledge score before and after health education intervention (P=0,0000) Respondents knouledge level before health education were 11 people have poor knowledge and 1 people have moderate knowledge. after health education intervention respondent knowledge level showing higer level that 11 poeple on mederate knowledge and 1 people have good knowledge. its mean that health education have effect to improve knowledge. The results of study are ex[ected to be considered by health care within adjust the appropriate programs in order to Diabetes patient can get knowledge about them disease and can do good practices of self management.